Defensive Approaches on SQL Injection and Cross-Site Scripting Attacks (Global Journal of Computer Science and Technology, 2014)
SQL Injection attacks are the most common attacks on the web applications Statistical analysis says that so many web sites which interact with the database are prone to SQL Injection XSS attacks Different kinds of vulnerability detection system and attack detection systems exist there is no efficient system for detecting these kinds of attacks SQL Injection attacks are possible due to the design drawbacks of the websites which interact with back-end databases Successful attacks may damage more The state-of-art web application input validation echniques fails to identify the proper SQL XSS Vulnerabilities accurately because of the systems correctness of sanity checking capability proper placement of valuators on the applications The systems fail while processing HTTP Parameter pollution attacks An extensive survey on the SQL Injection attacks is conducted to present various detection and prevension mechanisms